Mechanisms of Genome Maintenance in Plants: Playing It Safe With Breaks and Bumps - Raina, Aamir; Sahu, Parmeshwar K.; Laskar, Rafiul Amin; Rajora, Nitika; Sao, Richa; Khan, Samiullah; Ganai, Rais A. (Frontiers in Genetics, 2021)
Maintenance of genomic integrity is critical for the perpetuation of all forms of life including humans. Living organisms are constantly exposed to stress from internal metabolic processes and external environmental sources causing damage to the DNA thereby promoting genomic instability. To counter the deleterious effects of genomic instability organisms have evolved general and specific DNA damage repair (DDR) pathways which act either independently or mutually to repair the DNA damage. The mechanisms by which various DNA repair pathways are activated have been fairly investigated in model organisms including bacteria, fungi, & mammals, however very little is known regarding how plants sense and repair DNA damage. Plants being sessile are innately exposed to a wide range of DNA damaging agents both from biotic and abiotic sources such as UV rays or metabolic by-products. In order to escape their harmful effects plants also harbour highly conserved DDR pathways which share several components with the DDR machinery of other organisms. Maintenance of genomic integrity is key for plant survival due to lack of reserve germline since derivation of the new plant occurs from the meristem. Untowardly, accumulation of mutations in the meristem will result in wide range of genetic abnormalities in new plants affecting plant development and crop yield. In this review we will discuss various DNA repair pathways in plants and describe how deficiency of each repair pathway affects plant growth and development.